Microorganism Identification of Contaminant on Oil Palm (Elaeis guineensis Jacq.) Tissue Culture - Ilham, Muhammad; Ernayunita, Ernayunita; Yuli Rahmadi, Hernawan (Jurnal Penelitian Kelapa Sawit, 2025)
The issue of oil palm tissue culture is that the risk of microorganism contamination in its every process. Microorganism contamination can hinder the growth and development of explants, even causing them to fail to grow. The mostly types of contamination found in tissue culture are bacteria and fungi. Contaminating microorganisms can thrive in tissue culture media due to the presence of nutrients. This research aims to determine the type of contamination in oil palm tissue culture and, if necessary in the future, determine the use of antibiotics as a preventive measure against contamination in the tissue culture process. The research methods used purvosive sampling which included sample criteria, sample selection, sample verification followed by isolation, purification, and microscopic/macroscopic observation. The results revealed two genera from fungal isolates, namely Aspergillus sp. and Penicillium sp. through microscope observation with 1000x magnification. Additionally, four bacterial isolates were identified as gram-negative and one as gram-positive through the gram test using 3% KOH. The highest abundance of bacterial isolates was shown in sample 3, with 2,9 x 105 CFU/mL. Microscopic morphology included round (coccus), rod-shaped (bacillus), and spiral shapes. To control the microorganisms, antibiotics such as Tetracycline, Ciprofloxacin, and Kanamycin, as well as antifungals like fluconazole and ketoconazole. To prevent microorganisms is managed by sterilizing tools and materials, selecting sterilant substances, sterilization techniques, clean culture room conditions, monitoring and periodically removing contaminated cultures.